2008
DOI: 10.1038/jcbfm.2008.70
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Attenuates Neuroprotective Benefits of Isoflurane Preconditioning in Ischemic Mouse Brain

Abstract: Isoflurane preconditioning (IsoPC) neuroprotection in experimental stroke is male-specific. We determined whether estradiol alters ischemic outcomes in IsoPC brain and examined the role of estrogen receptors (ERs). Seven to 10 days before preconditioning, ovariectomized (OVX) mice were implanted with estradiol, vehicle, or ER subtype agonists. OVX ± estradiol, OVX ± vehicle, OVX ± ER agonists, and ER subtype wild-type (WT) and knockout (KO) mice were preconditioned for 4 h with sham anesthetic preconditioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 53 publications
1
24
0
1
Order By: Relevance
“…Oestrogen also increased infarct size after transient MCAO [32] and increased neuronal cell loss after forebrain ischaemia [33,34] in diabetic animals. Furthermore, oestrogen has been shown to attenuate the neuroprotective effects of isoflurane pre-conditioning in mice exposed to transient MCAO [35]. These studies highlight the potential for oestrogen to have detrimental effects where there is pre-existing disease, prior exposure to anaesthetics or other pre-conditioning stimuli.…”
Section: Beneficial and Detrimental Effects Of Oestrogen Alonementioning
confidence: 90%
“…Oestrogen also increased infarct size after transient MCAO [32] and increased neuronal cell loss after forebrain ischaemia [33,34] in diabetic animals. Furthermore, oestrogen has been shown to attenuate the neuroprotective effects of isoflurane pre-conditioning in mice exposed to transient MCAO [35]. These studies highlight the potential for oestrogen to have detrimental effects where there is pre-existing disease, prior exposure to anaesthetics or other pre-conditioning stimuli.…”
Section: Beneficial and Detrimental Effects Of Oestrogen Alonementioning
confidence: 90%
“…Other factors that could be involved are the suppression of energy requirements, inhibition of excitatory neurotransmission and potentiation of inhibitory receptors, regulation of intracellular calcium responses during ischemia, and the attenuation of ubiquitin-conjugated protein aggregation (36)(37)(38)(39). Surprisingly, recent animal studies have shown that isoflurane preconditioning response is attenuated by estradiol (40) and that is androgen-dependent in male mice and gender-specific (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Although being male is recognized as a risk factor for CI, some basic and clinical studies have shown the opposite results. 30,31 ATP, the ligand for P2RY2, has been shown to increase the production of progesterone and estradiol in human granulosa-luteal cells. 32 Several clinical and experimental studies have suggested that estrogen is not universally neuroprotective in experimental cerebral ischemia 31 and may not be beneficial for ischemic preconditioning in experimental ischemia models.…”
Section: Discussionmentioning
confidence: 99%